Strengthening the Education Cluster through Disaster-Safe Education Units (SPAB) in Disaster Management in Lebong Regency - Agus Widianto; Deby Harianto; Rekho Adriadi (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2026)
The floods in Lebong Regency, Bengkulu Province, in April and May 2026 exposed the vulnerability of educational institutions and showed that education disruption is not merely a school-level facility problem, but a public service governance issue. This article uses a qualitative, document-based case study to formulate a district-level Education Cluster strengthening model anchored in the Disaster-Safe Education Unit (SPAB) framework. The research gap addressed is the tendency of previous studies to examine post-disaster response or school preparedness separately, while the governance design that connects normal-time preparedness, emergency coordination, and learning recovery remains underdeveloped. Data were obtained from preliminary school loss records, policy documents, local news, and academic literature, then analyzed through open coding, thematic categorization, policy interpretation, and model synthesis. The findings identify three layers of vulnerability: physical school infrastructure, continuity of learning and evaluation, and inter-actor coordination. The novelty of this study lies in an absorptive and adaptive Education Cluster model that integrates a joint secretariat, education risk data, school early warning procedures, contingency plans, and pentahelix partnerships. The model positions the Education Cluster as a collaborative governance and resilience governance instrument to protect children’s right to learn before, during, and after recurring floods.